REFLEXÕES A PROPÓSITO DO TRATAMENTO RESERVADO PELO ESTADO BRASILEIRO AOS POVOS ORIGINÁRIOS: O POVO TUPINAMBÁ DE OLIVENÇA - Da Veiga Alves, Denise; Cupsinski, Adelar (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
Similar to historical patterns where non-indigenous populations based their interactions with indigenous peoples on the exploitation and destruction of natural resources in their habitats, along with their physical and symbolic subjugation and annihilation, these colonial relationships persist in contemporary times. This article borrows the category of genocide from BELTRÃO, defined as actions leading to the decimation and confinement of indigenous peoples in settlements, directories, indigenous colonies, or in indigenous posts established by the Indian Protection Service (SPI - Serviço de Proteção ao Índio) and later by the National Indian Foundation (Funai - Fundação de Proteção ao Índio). These actions aim to prevent them from continuing to live in their territories and reproducing socially as they did before the arrival of invaders, persisting continuously from colonial times to the present, denying their autonomy despite an ongoing history of struggles. In this context, the state’s omission, failure, or delay in fulfilling the duties outlined in Article 231 of the Brazilian Federal Constitution – whereby it is the responsibility of the Union to demarcate traditionally occupied lands, protect and enforce all assets of indigenous peoples, and recognize their social organization, customs, languages, beliefs, and traditions – constitutes another perverse variation of genocide practice. This exposes these peoples to successive violence, perpetrated by third parties or by state institutions themselves. This article compares the relational approach of the national society and the Brazilian state towards indigenous peoples with the historical experiences of the Tupinambá people of Olivença, highlighting their ongoing resistance against attacks and criminalization. This is particularly emphasized by Chief Babau Tupinambá of the Serra do Padeiro village, Rosivaldo Ferreira da Silva, who states, "genocide is ongoing."